Tedhak Siten dan Shichi-Go-San: Perbandingan Perayaan Anak dalam Tradisi Jawa dan Jepang - Puspita Sari, Indah (Javano Islamicus, 2025)
Every society in the world has certain celebrations to commemorate the cycle of human life. One of the celebrations that exist is a celebration devoted to children. The Javanese have a tedhak siten celebration to commemorate a child setting foot on the ground for the first time at the age of 7-8 months. The Japanese have Shici-Go-San celebrations to commemorate children at the age of 3, 5 and 7. The purpose of this paper is to compare the similarities and differences between tedhak siten in Java and Shici-Go-San in Japan, a celebration that is equally devoted to children. The method used is a qualitative method with data collection techniques in the form of literature study by reviewing books, journals and related articles. The theories used are transitional theory and symbolic theory. As a result, the similarity of these two celebrations is a celebration that contains prayers and hopes for the child's future by performing certain procedures and serving special foods that are full of meaning. The difference is that tedhak siten is done when the child is 7-8 months old in Javanese kalen-der held at home while Shici-Go-San is celebrated on November 15 for children aged 3, 5, and 7 at the temple.